Catholic Communities and Kinship Networks of the Elizabethan Midlands - Verner Laura (Perichoresis: The Theological Journal of Emanuel University, 2015)
An integral method of keeping a non-conforming community functioning is the construction and up keep of networks, as this web of connections provided security and protection with other non-conformists against the persecuting authorities. The non-conforming Catholic community of Elizabethan England (1558-1603) established various networks within England and abroad. This article is based on research that examines the network of Catholics in the Elizabethan Midlands in order to understand both its effectiveness and the relationship of the local and extended Catholic community with one another. The construction, function and result of these networks will be surveyed over several categories of networks, such as local, underground, clerical and exile. Members of the Midland Catholic community travelled to others areas of the British Isles and Europe to gather spiritual and material support for their faith, sent their children abroad for religious education, and resettled abroad creating in this wake a larger and complex international network. The main objective of this exercise is to show the dynamic and function of the network, and understand the impact it had at the local level for Midland Catholics.